Action Research in Moroccan English Language Teaching: Perceptions and Practices - Oubedda, Mohamed; Ouhejjou , Mohamed; Khalil Hsoune, Khalil Hsoune (International Journal of Language and Literary Studies, 2024)
Action research (AR) has increasingly been recognized as an effective means of bridging the gap between educational theory and classroom practice. However, its implementation in the Moroccan English Language Teaching (ELT) context remains limited. This study explores the perceptions and practices of action research among three key stakeholders: EFL teachers, teacher trainers, and supervisors. Using a qualitative exploratory design, data were collected through semi-structured interviews with 13 participants. The findings reveal that while all stakeholders hold positive attitudes toward AR and acknowledge its value for professional development and reflective practice, its actual implementation is sporadic and largely informal. This gap is mainly attributed to structural constraints, including heavy workload, limited research training, and lack of institutional support. The study also highlights a disconnect between pre-service training, where AR is formally introduced, and in-service contexts, where it is insufficiently integrated. The paper argues that promoting action research in Morocco requires stronger institutional support, practical training, and the development of collaborative professional cultures.